A simple way to graft a bioactive polymer – Polystyrene sodium sulfonate on silicone surfaces. (5th April 2020) - Lam, Mylan; Moris, Vivien; Humblot, Vincent; Migonney, Véronique; Falentin-Daudre, Céline
Graphical abstract: Highlights: A simple method to activate silicone surface and to graft bioactive polymers by using UV irradiation. Grafting of a bioactive polymer on silicone to allow a better integration of the implant. Characterization of the grafting of bioactive polymers on silicone surfaces. Abstract: Silicone-based materials are largely used in plenty of fields, especially in the biomedical field as implantable devices for surgery purposes. However, due to recent issues, the safety of the material has been reconsidered. In this work, we aim to graft a bioactive polymer on silicone breast implants shell surface to allow better integration of the implant inside the body and also a decrease of the bacterial adhesion. To functionalize silicone material, we develop a simple method to first activate the surface only using UV irradiation allowing then the radical polymerization of sodium styrene sulfonate to occur. Different parameters such as activation time, monomer concentration or sample size, have been studied to get optimum grafting rates. All along the grafting process, surfaces are characterized using ATR-FTIR, SEM-EDS, WCA measurements, colorimetric method, and XPS. Our results indicate that with the use of UV irradiation, it is thus possible both to activate and initiate the grafting of the bioactive polymer on silicone surfaces.